2019
DOI: 10.1021/acs.biochem.8b01147
|View full text |Cite
|
Sign up to set email alerts
|

The Anionic Phospholipids in the Plasma Membrane Play an Important Role in Regulating the Biochemical Properties and Biological Functions of RecA Proteins

Abstract: Escherichia coli RecA (EcRecA) forms discrete foci that cluster at cell poles during normal growth, which are redistributed along the filamented cell axis upon induction of the SOS response. The plasma membrane is thought to act as a scaffold for EcRecA foci, thereby playing an important role in RecA-dependent homologous recombination. In addition, in vivo and in vitro studies demonstrate that EcRecA binds strongly to the anionic phospholipids. However, there have been almost no data on the association of myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The western blot assay was performed as previously described . Protein samples (15 μL) were separated by SDS/PAGE, transferred to polyvinylidene difluoride membranes, blocked with 5% nonfat dry milk in Tris‐buffered saline and probed with either anti‐MtUvrB, anti‐MtUvrC or anti‐His antibodies at dilution 1 : 5000.…”
Section: Methodsmentioning
confidence: 99%
“…The western blot assay was performed as previously described . Protein samples (15 μL) were separated by SDS/PAGE, transferred to polyvinylidene difluoride membranes, blocked with 5% nonfat dry milk in Tris‐buffered saline and probed with either anti‐MtUvrB, anti‐MtUvrC or anti‐His antibodies at dilution 1 : 5000.…”
Section: Methodsmentioning
confidence: 99%
“…The smear or wrong bands located outside the target band position come from nonspecific amplification. 22 We found that new DNA strands with a length of 689 bp were successfully synthesized. Both BP and Pfu complexes of physical adsorption or chemical bonding could enhance the DNA replication efficiency (Figure 2c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The activated initiator protein DnaA at the cell membrane recognizes and binds the oriC site of the bacterial chromosome to initiate DNA replication. , When anionic phospholipids are depleted, the chromosomal replication of E. coli is inhibited. Although a lot of effort has been expended to investigate the DNA/membrane or polymerase/membrane complex of the bacteria, it is still unclear how the membrane assists in DNA replication. …”
Section: Introductionmentioning
confidence: 99%
“…The assay was carried out as described previously [37,67,68]. Briefly, the proteins from SDS/PAGE gels were transferred onto ethanol‐treated polyvinylidene difluoride membranes in a transfer buffer [20 m m Tris/HCl, pH 8, 190 m m glycine and 20% methanol] at 100 V for 1 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as described [67]. The reaction buffer containing 25 m m Tris/HCl (pH 7.5), 10 m m MgCl 2 , 2.5 m m DTT, 200 pmol [α‐ 32 P]ATP and increasing amounts of MtUvrC or EcUvrC was incubated at 37 °C.…”
Section: Methodsmentioning
confidence: 99%